Tosca - Puccini, Giacomo 1858-1924 (Dt. Grammophon, 2005)
Puccini's tragic opera about love and betrayal in Italy of the Napoleonic times.
Interpr.: Raina Kabaivanska, Floria Tosca. Placido Domingo, Mario Cavaradossi. Sherrill Milnes, il barone Scarpia. New Philharmonia Orchestra. Bruno Bartoletti [Dir.]. Gianfranco DeBosio [Regie]. - Aufn.: 1976. - Untertitel in ital., engl., dt., französ., span. und chines. Sprache
Keywords: Puccini, Giacomo <1858-1924> -- Film and video adaptations; Sardou, Victorien <1831-1908> -- Film and video adaptations; Puccini, Giacomo -- 1858-1924 -- Tosca; Film adaptations; Music videos; Musical films; Operas -- Film and video adaptations; Film; DVD-Video